2003
DOI: 10.1046/j.1365-2842.2003.01123.x
|View full text |Cite
|
Sign up to set email alerts
|

3‐D Finite element analysis of all‐ceramic posterior crowns

Abstract: The purpose of this study was to evaluate the stress distribution under various loading conditions within posterior all-ceramic crowns. A three-dimensional finite element model representing a lower first molar was constructed. Variations of the model had two types of single layer all-ceramic crowns (Dicor and Empress) and two types of double layer all-ceramic crowns (In-Ceram and Empress2) cemented. A load of 600 N, simulating the maximum bite force, was applied vertically to the crowns. Loads of 225 N, simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 13 publications
3
50
0
3
Order By: Relevance
“…However, DTS and FS are obtained in loading states that are not uniaxial and the results of these tests are not equivalent, as numerous previous works have shown for different dental materials (Ban & Anusavice, 1990;Probster et al, 1997;Xie et al, 2000). Despite this, DTS and FS have been used interchangeably in recent works as a reference to compare with computed maximal stresses in finite element models of dental restorations (De Jager et al, 2006;Imanishi et al, 2003). On analysing the stress state in both tests, FS seems preferable as a reference for the tensile strength of a ductile material because the stress state is uniaxial at the failure point, and this can only be said of a DTT if a plain stress state is assumed, which if far from being the actual situation in real tests.…”
Section: Interpreting Fea Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, DTS and FS are obtained in loading states that are not uniaxial and the results of these tests are not equivalent, as numerous previous works have shown for different dental materials (Ban & Anusavice, 1990;Probster et al, 1997;Xie et al, 2000). Despite this, DTS and FS have been used interchangeably in recent works as a reference to compare with computed maximal stresses in finite element models of dental restorations (De Jager et al, 2006;Imanishi et al, 2003). On analysing the stress state in both tests, FS seems preferable as a reference for the tensile strength of a ductile material because the stress state is uniaxial at the failure point, and this can only be said of a DTT if a plain stress state is assumed, which if far from being the actual situation in real tests.…”
Section: Interpreting Fea Resultsmentioning
confidence: 99%
“…Not all models in the literature include the bone. When included, sometimes it is modelled with uniform properties (Imanishi et al, 2003;Nakamura et al, 2006), although most of the models consider the cancellous bone and a layer of cortical bone near the bone surface Gonzalez-Lluch et al, 2009b). Thin structures, such as the PDL and cement are not always considered in the FE models.…”
Section: Components In the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, hybrid zirconia frames for crowns or fixed partial dentures need to be fabricated using the CAD/CAM system in such a way that the dense zirconia portion of the hybrid block is located at the lower part of the frame. This is because great stress is applied at the cervical area 8,9) of crowns or at the lower part 11) of the connectors of fixed partial dentures.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the largest stress is usually applied to the cervical area of the crown 9,10) or to the lower part of the connector of all-ceramic fixed partial dentures 11) . Therefore, we conceived of fabricating a hybrid zirconia frame made of both porous and dense zirconia (hereinafter called hybrid zirconia frame).…”
Section: Introductionmentioning
confidence: 99%